Perbandingan Ekstrak Empat Bahan Alam Terhadap Pertumbuhan Bakteri Staphylococcus Aureus - Fathimatus Safra; Aliyah Zahra; Mutiara Ratna Riris; Rahmalia Putri Khayla; Yonathan Tri Atmodjo Reubun (Jurnal Farmasi IKIFA, 2025)
Staphylococcus aureus is part of the normal flora of the human body and can be found in the oral cavity (both in individuals who use orthodontic equipment), skin, respiratory tract, and digestive tract, as well as in the air and surrounding environment. The mechanism of action of antibacterial compounds includes blocking cell wall formation and affecting integrity. The ability of bacterial cell walls, inhibition of enzyme activity, and failure to combine nucleic acids and proteins are some of the antibacterial mechanisms of lime leaves extracted using essential oil, which have anti-bacterial activity with a minimum bactericidal concentration (KBM) against Staphylococcus aureus of 0.625% v/v and Escherichia coli of 1.25% v/v. Red betel leaf extract at a concentration of 60% showed an inhibitory zone for Staphylococcus aureus bacteria with an average inhibitory zone diameter of 7.96 mm against Staphylococcus aureus with a significant value (P<0.05). The anti-bacterial activity of papaya leaf ethanol extract and this phytochemical test showed that the average diameter of the inhibition zone was 8.24 mm at a concentration of 80%, followed by 8.1 mm at a concentration of 60%, 6.7 mm at a concentration of 40%, 4.96 mm at a concentration of 20%, and 3.92 mm at a concentration of 10%.